Peningkatan Kapasitas Guru IPS dalam Mitigasi Bencana Melalui Komik Edukasi Berbasis Deep Learning di Kota Semarang - Mulianingsih, Ferani; Fajar, Fajar; Mumpuni, Restu Ayu; Kintoko, Kintoko (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Disaster mitigation is a critical component in the field of education, particularly for Social Studies (IPS) teachers who play a strategic role in fostering students’ awareness of disaster risks. This community service program aims to enhance the capacity of Social Studies teachers in Semarang City to deliver disaster preparedness material through educational comics supported by deep learning technology. The program’s approach involves intensive training on the development of digital educational comics utilizing artificial intelligence to produce adaptive and interactive narratives. Teachers are guided to comprehend the fundamental principles of disaster mitigation, integrate deep learning into visual material development, and refine their pedagogical delivery techniques. This approach is expected to generate an interactive comic-based learning method that improves teachers’ understanding and engagement in disaster education. Furthermore, the application of deep learning allows for greater personalization of content tailored to the specific learning context. Therefore, this program holds potential as an innovative, technology-oriented model for sustainable disaster mitigation education.